Advancing Public Health in Rwanda through the Field Epidemiology Training Program - Mutabazi Vincent,; Sinayobye Jean d’Amour (Journal of Interventional Epidemiology and Public Health)
We are pleased to present the latest edition of the Journal of Interventional Epidemiology and Public Health (JIEPH) special supplement featuring articles from the Rwanda Field Epidemiology Training Program (R-FETP). This edition covers critical public health issues in Rwanda, highlighting past efforts to combat the COVID-19 pandemic, address the challenges of HIV/AIDS, and improve maternal and child health. The articles offer valuable insights that can inform and inspire public health practitioners, policymakers, and researchers both in Rwanda and globally.